SISTEM INFORMASI PERPUSTAKAAN (SIPUSTAKA) MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Mundirin, Mundirin; Adistira, Muhammad Dezan (UNIVERSITAS STEKOM, 2024)
Library Information System at SMKN 13 Jakarta will be built to overcome various existing problems, such as the lack of information providers, difficulties in accessing books and magazines and lack of ease in searching bookshelf data. So it is necessary to create a Digital Library information system. This library information system was built using the PHP programming language, Sublime Text, Bootstrap, Java Script, CSS and MySQL database. The development method used is the Rapid Application Development (RAD) method. The presence of this library information system is expected to make it easier for library staff, school principals and library members in managing data about the library, and also for members to make reading and borrowing books easier.